2012
DOI: 10.1080/09593330.2011.618935
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of pullulan-degradingAnoxybacillusspecies isolated from Malaysian hot springs

Abstract: Two thermophilic bacteria (SK3-4 and DT3-1) were isolated from the Sungai Klah (SK) and Dusun Tua (DT) hot springs in Malaysia. The cells from both strains were rod-shaped, stained Gram positive and formed endospores. The optimal growth of both strains was observed at 55 degrees C and pH 7. Strain DT3-1 exhibited a higher tolerance to chloramphenicol (100 microg ml(-1)) but showed a lower tolerance to sodium chloride (2%, w/v) compared to strain SK3-4. Phylogenetic analysis based on 16S rRNA gene sequences rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 27 publications
0
30
1
Order By: Relevance
“…Isolation of microorganisms Two Anoxybacillus strains, SK3-4 and DT3-1, respectively, were isolated from water samples that were taken from the SK and DT hot springs in Malaysia [7]. The NCBI accession numbers for the 16S rDNA sequences are GQ184213 and GU129931.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolation of microorganisms Two Anoxybacillus strains, SK3-4 and DT3-1, respectively, were isolated from water samples that were taken from the SK and DT hot springs in Malaysia [7]. The NCBI accession numbers for the 16S rDNA sequences are GQ184213 and GU129931.…”
Section: Resultsmentioning
confidence: 99%
“…However, their pigmentation and colony and individual cell sizes were dissimilar. Additionally, the 16S rDNA sequences, fatty acid profiles, and DNA G?C contents revealed that the strains were distinct [7]. Despite the differences in cell morphology and biochemical characteristics, the sequences of the amylase genes are quite similar.…”
Section: Introductionmentioning
confidence: 96%
“…SK3-4 was isolated from a Malaysian hotspring28 and its genome was sequenced using Illumina MiSeq29. Most of the glycoside hydrolases of the cell are expressed intracellularly; however, ASKA was described as an extracellular hydrolase18.…”
Section: Discussionmentioning
confidence: 99%
“…DT3-1 was grown on solid (15 g/L agar) or liquid media containing 4.0 g/L of peptone, 4.0 g/L of tryptone, 4.0 g/L of yeast extract, 2.0 g/L of NaCl, and 1.0 g/L of MgSO 4 , as reported previously [18]. Genomic DNA was purified using the Wizard Genomic DNA Purification Kit (Promega, Madison, USA).…”
Section: Methodsmentioning
confidence: 99%
“…DT3-1 (DSM 28778) is a thermophilic bacterium which was isolated from a Malaysian hot spring of a temperature of 75 °C [18], where its genome has been sequenced. A putative BGL (GH1) identified (UniProtKB M5QUM2) in Anoxybacillus sp.…”
Section: Introductionmentioning
confidence: 99%